Poligami dalam Perspektif Islam dan Praktiknya di Luar Islam: Tinjauan Maqāṣid al-Syarī‘ah - Sirojudin (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This article discusses polygamy from the Islamic perspective and the practice of polygamy outside Islam using an analytical approach. The study emphasizes the relationship between the permissibility of polygamy and the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly the preservation of lineage (ḥifẓ al-nasl), which can only be achieved through the fulfillment of strict conditions and requirements. In addition, this article elaborates on various wisdoms of polygamy, both in terms of moral protection and social welfare. The findings indicate that polygamy in Islam is not intended as a source of problems, but rather as a sharī‘ah-based solution in certain circumstances, provided that it is practiced in accordance with the fundamental objectives of Islamic law. This study is expected to provide a more complete and comprehensive understanding for the public regarding the concept of polygamy. Keywords: Polygamy, Maqāṣid Al-Sharī‘Ah, Ḥifẓ Al-Nasl, Islamic Law, Social Welfare. Abstrak Tulisan ini membahas poligami dalam perspektif Islam dan praktik poligami di luar Islam dengan pendekatan analitis. Kajian ini menekankan keterkaitan antara kebolehan poligami dan maqāṣid al-syarī‘ah, khususnya dalam menjaga keturunan (ḥifẓ al-nasl), yang hanya dapat diwujudkan melalui pemenuhan syarat dan ketentuan yang ketat. Selain itu, artikel ini menguraikan berbagai hikmah poligami, baik dari aspek perlindungan moral maupun kemaslahatan sosial. Hasil kajian menunjukkan bahwa poligami dalam Islam tidak dimaksudkan sebagai sumber masalah, melainkan sebagai solusi syariat dalam kondisi tertentu, sepanjang dijalankan sesuai dengan tujuan dasar hukum Islam. Kajian ini diharapkan dapat memberikan pemahaman yang lebih utuh dan komprehensif kepada masyarakat mengenai konsep poligami. Kata kunci: Poligami, Maqāṣid Al-Syarī‘Ah, Ḥifẓ Al-Nasl, Hukum Islam, Kemaslahatan Sosial